Experimental study on the reinforced fly ash and sand retaining wall under static load. (10th July 2020) - Li, Li-Hua; Yu, Chang-Dao; Xiao, Heng-Lin; Feng, Wei-Qiang; Ma, Qiang; Yin, Jian-Hua
Highlights: Nine physical model tests were conducted for the deformation and ultimate bearing capacity of the retaining wall. The combination of geogrid and waste tire reinforcement is recommended for retaining wall. Wu and Pham's model is suitable for different reinforcement materials in physical model tests. Fly ash is suitable to be used as the fill materials of retaining wall in geotechnical engineering. Abstract: Fly ash is a sustainable fill material used in retaining structures. Physical model tests were conducted to investigate the deformation characteristics and ultimate bearing capacity of a retaining wall consisting of a fly ash-sand mixture backfill and geosynthetic reinforcements. Different types, layers, and combinations of geogrid materials including the waste tires were considered in the physical model tests. The vertical earth pressure and displacements of the retaining wall were monitored for various surcharge loads. The results indicated that a reinforced layer effectively increases the bearing capacity of the retaining wall and decreases vertical settlement and deflection. Furthermore, waste tires exhibited greater deformation resistance and bearing capacity compared to other materials. Waste tire and geogrid combinations help to uniformly distribute the surcharge load and improve retaining wall performance. Finally, two analytical models were compared to the experimental results to access their feasibility for various reinforcement materials and combinations.